Danza en la Puna - Baldo, Jorge; Arzamendia, Yanina; Rojo, Verónica; Vilá, Bibiana (Revista Aves Argentinas, 2021)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).